The importance of liquidity to improve the quality earnings of company - Teguh Erawati; Hadri Kusuma; Titi Swantari; Reni Listyawati (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
This research aims to examine the relationship of Profitability, Liquidity, and Investment Opportunity Set on Earnings Quality with Good Corporate Governance as its Moderating Variable from some manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The sampling technique employed in this study is purposive sampling method by observing a total of 57 manufacturing companies, so that the total samples were 285 data. The results of this study indicate that the profitability variable has no positive effect on earnings quality; the liquidity variable has a positive effect on earnings quality; and the IOS variable has no negative effect on earnings quality. In addition, the Good Corporate Governance (GCG) variable is unable to moderate the profitability variable on earnings quality. The GCG variable is also unable to moderate the liquidity variable on earnings quality. However, the GCG variable is able to moderate the IOS variable on earnings quality.